Bacterial Vaginosis and Trichomononiasis. Fundamental World Guidelines on Management and Therapy of the Patients - M. A. Gomberg (Антибиотики и Химиотерапия)
The vaginal discharge is one of the most frequent symptoms requiring medical advise. Vaginal discharges are mainly associated with three diseases: bacterial vaginosis, trichomononiasis and candidiasis. The review is concerned with up-to-date approaches to the treatment of females with bacterial vaginosis and trichomononiasis, diseases different by the etiology and pathogenesis, but at the same time similar with respect to the treatment. The analysis is in compliance with the principles of the two fundamental world guidelines.